Penggunaan Media Interaktif untuk Pengenalan Huruf Hijaiyah Pada Santri di Balai Pengajian Nurul Hidayah Al-Hanafiah Bireuen - Sriwinar; Iskandar Zulkarnaini; Iqbal (LPPM Umuslim, 2022)
This service aims to improve the ability to read hijaiyah letters by using interactive media for students of the Nurul Hidayah Al-Hanafiah study center, Bireuen Regency. The ability to read hijaiyah letters that is learned is to read hijaiyah letters at random and distinguish hijaiyah letters which are almost similar in shape. The subjects of this service are 25 students of the Nurul Hidayah Al-Hanafiah Study Center from April 18 to May 8, 2022. The object of this service is the ability to read hijaiyah letters using interactive media. Data collection techniques through observation. The results of the service, students can master and recognize hijaiyah letters and help ease the work of the ustadz in teaching students at the Nurul Hidayah Al-Hanafiah Bireuen study hall.